Image-based tree detection for autonomous navigation in orchards - Cadenat, V.; Durand-Petiteville, A.; Billot, D.; Villemazet, A. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This paper deals with the autonomous navigation problem through orchards. It highlights the different challenges arising in this particular environment and proposes an adequate framework. This latter relies on a reactive control strategy fed by visual data provided by a set of RGB-D cameras adequately positioned to enlarge the field of view. In this work, we show interest in coupling a deep learning solution for image-based detection with an existing point cloud processing algorithm to improve the overall perception. Experimental results validate the approach.